FREQUENCY AND MANAGEMENT OUTCOME OF PNEUMOTHORAX PATIENTS - Khan, Nisar; Jadoon, Huma; Zaman, Munawar; Subhani, Aqeel; Khan, Abdur Rab; Ihsanullah, Mian (Journal of Ayub Medical College Abbottabad, 2009)
Background: Primary spontaneous pneumothorax is a common clinical problem and its incidence is thought to be increasing. This study was conducted to see the frequency, aetiology, presentation and management outcomes of pneumothorax in patients presenting at Pulmonology unit, Ayub Teaching Hospital, Abbottabad, Pakistan. Methods: Pneumothorax patients reporting at the Pulmonology unit of Ayub Teaching Hospital, Abbottabad from 2002 to December 2008 were included in the study. Patients of all ages were included. They were admitted and followed up to the full recovery. Results: A total of 195 pneumothorax patients reported during this period. Majority of the patients were diagnosed to have pneumothorax due to pulmonary tuberculosis making about 36.92% of the total cases. Second most common cause was primary spontaneous pneumothorax (21.53%). COPD were also sizeable at 8.71%. Other causes included Bacterial infections, Asthma, iatrogenic, interstitial lung disease, bronchiectasis and Trauma. Conclusion: It was concluded from this study that pulmonary tuberculosis is the commonest cause of pneumothorax in our setup. Keywords: Primary spontaneous Pneumothorax (PSP), Secondary spontaneous Pneumothorax (SSP), Tuberculosis, Pulmonary, Lung diseases, Obstructive.